Health sciences libraries: strategies in an era of changing economics. - Messerle, J (1987)
Libraries in health care settings reflect their parent institutions, which, in turn, are affected by environmental changes. The economic climate of the 1980s, unleashing competitive forces and threatening the survival of some institutions, has had a major impact on both hospitals and academic health centers. The challenge to libraries of these institutions calls for reassessment of programs and realignment in their power structures. It is argued that libraries which position themselves to capitalize on the current economic environment will create a future with new opportunities.